IDENTIFYING INADEQUATE RESPONSE AMONG CROHN'S DISEASE PATIENTS ON A BIOLOGIC IN A REAL-WORLD ADMINISTRATIVE CLAIMS DATABASE. (21st January 2021) - Hunter, Theresa; Naegeli, April; Grabner, Michael; Isenberg, Keith; Shan, Mingyang; Teng, Chia-Chen
Abstract: Objectives: The purpose of this analysis was to assess the frequency of inadequate response (IR) over 1 year from biologic initiation among Crohn's disease (CD) patients in the United States using a claims-based algorithm. Baseline factors associated with IR to a biologic were also analyzed. Methods: This was a retrospective cohort study using claims data from the HealthCore Integrated Research Database. Adult patients with CD who initiated a biologic (TNFi: adalimumab, certolizumab, infliximab; non-TNFi: natalizumab, ustekinumab, and vedolizumab) from 7/1/2016 to 8/31/2018 and had continuous enrollment ≥6 months before and ≥12 months after index date (date of first biologic claim) were included. The index biologic was defined as the first biologic prescribed during the study time period. The claims-based algorithm used in this study to identify IR was originally developed and validated in rheumatoid arthritis and was modified for CD patients. Patients were identified as having IR to their index biologic if during the 12 months after index date they had one or more of the following: low adherence (defined as proportion of days covered (PDC)<80%), switched/added new biologic, added a new conventional therapy, increased dose/frequency of biologic, addition or dose increase of oral glucocorticoids, used a new pain medication, or had surgery for CD. Baseline patient characteristics were compared between responders and IRs using Chi-square tests for categorical variables and t-tests for continuous variables. A multivariable logistic regression model was constructed to identify baseline characteristics associated with IR to the index biologic. Results: A total of 2, 437 CD patients were included in this analysis. Mean age was 41 years, 53% were female, 81% initiated a TNFi, and 19% initiated a non-TNFi as their index biologic (Table 1). Over the 1-year follow-up period, 62% of CD patients had an IR to their biologic: 41% of patients had low adherence, 14% switched/added a new biologic, 13% added a new conventional therapy, 12% had a dose/frequency increase of their index biologic, 12% had an addition/dose increase of oral glucocorticoids, 8% used a new pain medication, and 5% had surgery. Inadequate responders were more likely to be female (odds ratio (OR)=1.36; p<0.001), have historical use of TNFi (OR=1.94; p<0.001), and be on a consumer-driven health plan (OR=1.28; p<0.001); while patients with baseline use of conventional therapy were more likely to be responders (OR=0.72; p<0.001) (Table 2). Conclusion: Over 62% of CD patients had an inadequate response to their index biologic within 1 year after initiation, mostly driven by low adherence. This modified claims-based algorithm for CD appears useful to classify inadequate responders in health plan claims data. Additional research is needed to further validate this algorithm in a clinical setting.